Стимулювання ефективної зайнятості в умовах поширення соціальної вразливості - Левицька, О. О.; Мульска, О. П.; Іванюк, У. В.; Levytska, O.; Mulska, O.; Ivaniuk, U. (Видавництво Львівської політехніки, 2023)
Обґрунтовано, що основні виклики сучасної сфери зайнятості в Україні призводять до збільшення зовнішньої міграції, зокрема, формування дефіциту робочої сили на національному ринку праці, посилення деструктивних змін у зайнятості; низька оплата, особливо працівників бюджетної сфери. Аргументовано, що реалізація інструментів стримування інструментів зовнішніх міграційних процесів виступає одним із напрямів державної політики зайнятості України. Доведено об’єктивна необхідність реалізації ефективних інституційно-адміністративних, організаційно-економічних та інформаційних інструментів державної політики зайнятості, яка корелює із мірою поширення соціальної вразливості, інтенсивністю зовнішніх міграційних процесів та зниження рівня прекаріату в Україні.

The purpose. The purpose of the article is to substantiate the need to improve the modern state employment policy under the intensification of external migration of the population of Ukraine. Effective institutional-administrative, organizational-economic, and information tools of the state employment policy should be used to create and improve the quality of existing jobs, intensify employment in rural areas, eliminate shadow employment and wages, equalize imbalances in supply and demand in the labor market. Design/Methodology/Approach. To study the need to develop modern state employment policy in Ukraine, the authors used the following research methods – theoretical and logical explanation, statistical analysis, systematization and explanation, semantic analysis. The study was conducted within the framework of institutional economic theory, migration, and state regulation of the economy. Findings. The studies have shown that the containment of external migration processes by increasing the number and improving the quality of jobs, in connection with which the task of developing the state employment policy against the background of high migration activity of the population of Ukraine is relevant. It is substantiated that the main challenges of the modern sphere of employment in Ukraine lead to an increase in external migration, namely: formation of labor shortage in the national labor market, intensification of destructive changes in employment; low pay, especially for budget sphere workers, the spread of shadow employment schemes, which leads to a decrease in social protection of employees; strengthening of professional and qualification imbalance in demand and proposals in the labor market due to the mismatch in training the specialists for the needs of the economy. Other challenges are the unformed labor market in rural areas, preservation trends of open and hidden unemployment among the rural population, reducing the demand for labor in rural areas; lack of appropriate conditions for the development of inclusive labor market, the insufficient realization of opportunities and potential of the state employment services in ensuring the innovative development of employment. The objective necessity of realization of effective institutionaladministrative, organizational-economic, and information tools of the state employment policy is proved, which largely depends on the natural containment of migration processes in Ukraine. The implementation of the presented tools is focused on economic stabilization of the situation in the country and regions by stimulating the de-shadowing of business and income, increase the welfare of the population, increase of opportunities for young people in employment, and the growth of aspirations of migrant workers to remigration and realization of own business goals on the territory of Ukraine. Practical implications. The materials presented in the article can help improve the state employment service activities and improve local, regional, state employment policy. Originality/value. The value of the research lies in the development of the mechanisms to ensure the competitiveness of national and regional labor markets as a tool for regulating external labor migration, as well as for improvement of the state employment policy, especially the development of innovative and creative types of work
Stimulation of effective employment in the conditions of social vulnerability
Keywords: сприяння зайнятості; соціальна вразливість; міграційні процеси; державна політика зайнятості; employment promotion; social vulnerability; migration processes; state employment policy; 331.556; 314.04